Determination of Factors Affecting Cashless Payment Through E-Wallet for Students in Yogyakarta - Pratama, Aditya Wahyu; Nasrulloh, Rifqi Syarif (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: This study aims to determine what factors can affect cashless payments to students in Yogyakarta. This research is important because there is a research gap from previous studies.Methodology: This study used a purposive sampling technique and the data collection technique used was distributing questionnaires to respondents by a Google Form with answers using 5-point Likert scale. A sample of 108 respondents was obtained. The collected data were analyzed using the SEM-PLS method with the help of SmartPLS 4 Software.Finding: The empirical test results showed that consumer knowledge had no effect on cashless decisions nor was it mediated by service features. Meanwhile, convenience had a significant positive effect on cashless decisions and service features were able to mediate the relationship between convenience and cashless decisions. Furthermore, service features had a significant positive effect on cashless e-Wallet decisions for students in Yogyakarta.Conclusion: Having a high level of knowledge did not increase student decisions to pay in cashless, this indicates a low level of community literacy. This finding can be interpreted that students feel that the e-Wallet cashless payment service features are easy to access, have various transaction features and services, and the many product innovations provided by e-Wallet can influence students to decide to pay cashless.